Differences in Perception and Diction on Two Translations Lelaki Tua dan Laut from Ernest Hemingway’s The Old Man and The Sea - Lina Meilinawati Rahayu (Humaniora, 2016)
Translation of literary work is never simply the business of translating the work in the source language into the target language. Translation is always culture-sensitive, as it also means translating the source culture into the target culture. This study examines two translations of the novel The Old Man and The Sea (1952) by Ernest Hemingway in the Indonesian language. Both are titled Lelaki Tua dan Laut. The earlier  was published in 1973 and was translated by Sapardi Djoko Damono, while the latter was translated by Dian Vita Ellyati and was published in 2010. These two translated versions are compared with each other in order to identify differences in perception and diction. Differences in diction further influence the reader’s perception. Close examination of the two versions discovers contrasting perception and diction. The study finds that Djoko Damono’s translation builds meaning by using Indonesian equivalents to represent the concepts presented in the novel, while Ellyati’s builds meaning through description and explanation of said concepts. Djoko Damono’s translation attempts to maintain poetic expressions through the use of rhyming words; Ellyati’s translation goes for clarity of meaning. Djoko Damono’s translation uses extensive vocabulary with specific meanings, while Ellyati’s chooses to employ words with more generic meanings. These differences indicate that translation work is never final; it is an ongoing, ever changing process.